The Minimally Invasive Approach to Appendectomy: Is Less Better? - Iqbal, Corey W.; Ostlie, Daniel J. (European Journal of Pediatric Surgery, 2012)
The benefits of the three-port laparoscopic appendectomy (TPLA) are now appreciated. Included in these advantages are reduced postoperative pain, reduced hospitalization, early return to routine activities, and a definite cosmetic benefit over the open approach. Recently, the single-incision laparoscopic technique for several disease processes has been popularized. The single-incision approach through the umbilicus is ideally suited for patients with nonperforated appendicitis. This article will review our operative technique for both the TPLA and single-incision laparoscopic appendectomy, and then review the available literature that compares benefits of one approach over the other. When comparing these two approaches, variables that will be discussed include infectious complications, operative time and cost, and the need for postoperative pain medication.
Keywords: appendectomy; appendicitis; laparoscopy; single-incision laparoscopic appendectomy; pediatric literature